CRITICAL ASSESSMENT OF THE CURRENT STATE OF ACCOUNTING AND AUDIT OF INTANGIBLE ASSETS AT ENTERPRISES - YEREMIAN ОLENA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Expansion of the use of intangible assets, imperfection of the legal framework and classification of objects, insufficient development of valuation methods, necessitates the improvement of their accounting and auditing. Today, the problem of developing a scientifically sound classification of intangible assets is of particular importance, which is an important prerequisite for the rational organization of accounting for this object. A critical analysis of the composition of these groups in the classification of intangible assets in accordance with UAS 8, which is the basis of sub-accounts of account 12 "Intangible assets", shows the existence of a number of inaccuracies. An important problem that needs to be solved in the process of organizing the accounting of intangible assets is the choice of forms of primary documents. The lack of standard forms of primary documents developed for intangible assets, as an accounting group of enterprise assets, does not meet modern requirements, which today are increasingly involved in business. The article, based on the study of foreign experience in the use and reporting of intangible assets, as well as its comparison with domestic enterprises, identifies the main problems associated with the use and accounting of intangible assets, and offers recommendations for their solution. The above problems are present in almost every domestic enterprise and lead to violations of the accounting process, insufficient coverage in the reporting of information on intangible assets, inaccurate assessment. The lack of valuation methodology does not allow to unambiguously determine the place of this type of economic resources in the accounting process, to represent them in the public reporting of the enterprise, especially to include them in the balance sheet to balance market and book value. Today, one of the pressing issues is to establish the value and impact of intangible assets on the market value of the enterprise. There is a need for in-depth study of existing and disputed intangible assets, the factors that affect them, the establishment and development of approaches, methods in order to objectively assess the value of the enterprise. In order to eliminate and prevent errors in the accounting of intangible assets and ensure quality audit of intangible assets in the enterprise, the article conducted a study of information support audit of intangible assets. Also, one of the promising areas of accounting and auditing of intangible assets is their implementation in the use of computer technology. Thus, the analysis of the results of research of domestic and foreign economists shows that theoretical and practical developments in accounting and auditing of intangible assets are modern and require further research and development to improve and adapt to international standards.